Analisis Faktor - Faktor yang Mempengaruhi Keputusan Pembelian Fried Chicken - Samuel Natamaro Purba; Mariana Simanjuntak (Lembaga Pengembangan Kinerja Dosen, 2024)
In the competitive fried chicken industry, understanding factors such as quality, price, promotion, brand image, and health considerations is essential for companies to stay competitive and meet customer expectations. This study aims to examine the influence of factors such as product quality, price, promotion, brand image and health considerations on the decision to purchase fried chicken products. This study uses a combined approach of qualitative descriptive research design and quantitative survey. The study population is consumers who often buy fried chicken, with a sample of 50 people selected through purposive sampling. Data analysis was carried out by multiple linear regression using SPSS software to identify significant factors in the decision to purchase fried chicken. Based on the results of the SPSS analysis, it can be concluded that the variables of product quality, price, promotion, and brand image have a significant positive effect on purchase decisions, while health variables do not have a significant influence on purchase decisions.